2020
DOI: 10.3390/brainsci10060393
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind Deficits and Neurophysiological Operations in Autism Spectrum Disorders: A Review

Abstract: Theory of Mind (ToM) is a multifaceted skill set which encompasses a variety of cognitive and neurobiological aspects. ToM deficits have long been regarded as one of the most disabling features in individuals with Autism Spectrum Disorder. One of the theories that attempts to account for these impairments is that of “broken mirror neurons”. The aim of this review is to present the most recent available studies with respect to the connection between the function of mirror neurons in individuals with ASD and ToM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 75 publications
2
38
0
1
Order By: Relevance
“…Here, we employed a novel experimental system designed for directly monitoring social investigation behavior to examine the behavior of these mice in a battery of four social discrimination tests. Of these tests, the ESP test is a novel test, which is similar in principle to the affective state discrimination test recently described (12), and seems to be highly relevant to ASD symptoms which involve impaired theory of mind (22,23). In agreement with our previous paper, we found normal behavior of A350V mice in the SP test which assesses social motivation, as well as in the SNP test which assesses social cognition.…”
Section: Discussionsupporting
confidence: 90%
“…Here, we employed a novel experimental system designed for directly monitoring social investigation behavior to examine the behavior of these mice in a battery of four social discrimination tests. Of these tests, the ESP test is a novel test, which is similar in principle to the affective state discrimination test recently described (12), and seems to be highly relevant to ASD symptoms which involve impaired theory of mind (22,23). In agreement with our previous paper, we found normal behavior of A350V mice in the SP test which assesses social motivation, as well as in the SNP test which assesses social cognition.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, progress in investigating complex symptoms of ASD patients has lagged, owing to inherent limitation of traditional behavioral analyses. For instance, the lack of emotional reciprocity is frequently observed in ASD patients, who have difficulty in performing a set of executive functions, including impaired theory of mind, imitation, or joint attention of other people [ 6 , 7 ]. Deficits in these higher cognitive functions, particularly, empathy, are likely to lead to abnormalities in complex social behaviors, such as social competition and cooperation [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the lack of emotional reciprocity is frequently observed in ASD patients, who have difficulty in performing a set of executive functions, including impaired theory of mind, imitation, or joint attention of other people [ 6 , 7 ]. Deficits in these higher cognitive functions, particularly, empathy, are likely to lead to abnormalities in complex social behaviors, such as social competition and cooperation [ 6 , 7 ]. Indeed, major symptoms of high-functioning autism include empathic incapacity, reactive aggression and impaired complex social behaviors [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study in ADHD patients versus healthy controls by Abdel-Hamid et al, 2019 [47], found significant positive correlations between theory of mind (ToM) and empathy competences and EF performances in the ADHD group but not in the control group. In a recent review, which analyzed fifteen studies conducted on ADHD samples, with or without comorbidities and included mostly male children, Pineda-Alhucema et al, 2018 [48], found the EF most correlated with ToM were inhibitory control, working memory, cognitive flexibility and attention (for further updated details on the relationship between EF and ToM please refer to Andreou et al 2020 [49]).…”
Section: Introductionmentioning
confidence: 99%